1987
DOI: 10.1021/np50052a021
|View full text |Cite
|
Sign up to set email alerts
|

Cedronin and 7-epi-Cedronin: X-ray Crystal Structure Analysis

Abstract: hTrlACT.--The structure and stereochemistry of the quassinoid cedronin 111 and the previously unreported 7-epi-cedronin 121 isolated from Simaba redron have been established by X-ray crystal structure analysis. The change in configuration at C-7 produces a minimal change in molecular conformation and crystal packing. Cedronin [7-epi-cedronin] crystallizes in the monoclinic space group P2, with cell parameters a=6.794(2) [6.779(1)1, b= 18.684$2) [19.029(3)], r=7.573(2) [7.419(2)]& p= 116.67(2)" [115.56(1)7, U=… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1989
1989
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 4 publications
(5 reference statements)
0
3
0
Order By: Relevance
“…The calculated results demonstrated that ring A adopted the conformation closer to the flattened chair rather than to the half-boat in which the approximate plane of symmetry passed through C(3) and C (10). The distorted half-boat of ring A was also supported by the torsion angles of Φ 1,2,3,4 = 3.2°and Φ 2,3,4,5 = −1.0° [27]. Furthermore, molecular modeling calculations were performed on 1 using the MM2 force field from Chem3D Ultra 9.0 (Cambridge-Soft) in order to determine the ring conformations.…”
mentioning
confidence: 82%
See 1 more Smart Citation
“…The calculated results demonstrated that ring A adopted the conformation closer to the flattened chair rather than to the half-boat in which the approximate plane of symmetry passed through C(3) and C (10). The distorted half-boat of ring A was also supported by the torsion angles of Φ 1,2,3,4 = 3.2°and Φ 2,3,4,5 = −1.0° [27]. Furthermore, molecular modeling calculations were performed on 1 using the MM2 force field from Chem3D Ultra 9.0 (Cambridge-Soft) in order to determine the ring conformations.…”
mentioning
confidence: 82%
“…In a similar manner, the flatten- 17, 111.77° (19), 110.20° (17) and 118.94° 17, respectively. Maximum torsion angle of 73.3°(Φ 8,9,11,12 ) supported the distorted chair of ring C [27]. Furthermore, the corresponding endocyclic torsion angle measurements (ΔC s 9,13 = |Φ 8,9 + Φ 9,11 | + |Φ 8,14 + Φ 11,12 | + |Φ 13,14 + Φ 12,13 | = 12°) [26] suggested that the approximate plane of symmetry of the flattened chair form of C passed through C(9) and C (13).…”
mentioning
confidence: 89%
“…'~~ The structure of 7-epicedronin (198), which occurs with cedronin (199) in S. cedron, has been established by X-ray analysis. 186 The neoquassin derivative (200) has been isolated from Quassia amara.18' Quassin and several of its congeners in the root bark of Picrasma quassioides show acute insecticidal activity against the American cockroach.la8 During this study a new compound, 14P-hydroxypicrasin (20 l), was isolated.188 Attempts to oxidize quassin with Jones' or Collins' reagents afforded the unexpected product (202) whose structure was established by X-ray analysis.1aa The details of the crystal structure analysis of bruceine B have appeared. lgo The antimalarial activity of some quassinoids is dependent on the nature of the ester group attached to C-15.1g1 Methods for converting inactive quassinoids into cytotoxic compounds by introduction of acyl or alkyl substituents at C-15 have been described.lg2…”
Section: Quasinoidsmentioning
confidence: 99%